Piperine inhibits biofilm formation and efflux activity and dysregulates lipid metabolism in Mycobacterium abscessus - Toe Ko Ko Htay; Matthew R. Hathaway; Jaiyanth Daniel (PLoS ONE, 2026)
The nontuberculous Mycobacterium abscessus is a human pathogen that causes chronic lung infections and soft tissue infections. The bacterium forms biofilms and efflux pumps contribute to its tolerance of antibiotics. Efflux pumps also transport lipids and other molecules to the bacterial outer cell surface for biofilm formation. The effects of piperine, an alkaloid derived from black pepper, on biofilm formation, efflux activity and lipid biosynthesis in M. abscessus have not been reported. We report that, at sub-minimum inhibitory concentration levels, piperine inhibits biofilm formation in M. abscessus by more than 90%. We investigated lipid biosynthesis from exogenously supplied radiolabeled 14 C-palmitic acid in M. abscessus during its log-phase growth and during biofilm formation and examined the effects of piperine. We report that piperine dysregulates the biosynthesis of major lipids in M. abscessus during biofilm formation. Piperine inhibited the biosynthesis of the neutral storage lipid triacylglycerol during biofilm formation by nearly 80% and the biosynthesis of the polar lipid trehalose monomycolate by 50%. In contrast, piperine stimulated the biosynthesis of the major polar lipid phosphatidylethanolamine during biofilm formation. Piperine inhibited efflux activity in M. abscessus by nearly 70%. Piperine enhanced the efficacies of four commonly used antibiotics used to treat M. abscessus infections. The minimum inhibitory concentration of clarithromycin was decreased by more than 16-fold by piperine and that of amikacin and cefoxitin by about 5-fold. The efficacy of ciprofloxacin was improved by more than 2-fold by piperine. This is the first report on the effects of piperine on lipid biosynthesis, efflux activity and biofilm formation in M. abscessus that highlights the potential importance of piperine as an adjunct therapy to treat nontuberculous mycobacterial infections.